Assessment Of Primary School Science Teachers’ Technological Pedagogical Content Knowledge (Tpack) In Sarawak - Bashela Carol, Roger (Universiti Malaysia Sarawak (UNIMAS), 2019)
Technological pedagogical content knowledge (TPACK) is the knowledge required for effective technology integration in teaching. TPACK assessment is important for teachers to understand their level of knowledge of technology integration in teaching. Since there were not much research on TPACK in Malaysia, the researcher conducted this study that focused on primary school teachers in Sarawak. In this study, Sarawak primary Science teachers’ TPACK was assessed through an online survey. The participants were selected randomly in Kuching and Bau districts in Sarawak. The data and its analysis revealed that the primary Science teachers in general had a positive perception of their understanding of TPACK. It is an indication that primary Science teachers in Sarawak perceived themselves as being able toteach with technology effectively. Geographical factors such as school location and demographic factor such as gender has no significant influence to Sarawak primary school Science teachers’ TPACK. However, there was a significant difference between teaching experience with the teachers’ TPACK. Regression analyses revealed that Technological Pedagogical Knowledge (TPK) made statistically significant unique contributions to Technological Pedagogical Content Knowledge (TPACK) thus it is recommended that educational establishment to organize professional development trainings that focus on the TPK elements of science subject.